Pengenalan Worksheet Mathematic Berbasis Budaya Aceh - Zahari, Cut Latifah; Sari, Dwi Novita; Ramadhani, Ramadhani; Siregar, Irwan Efendi; Utami, Sri Ulfa (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2022)
This community service program (PKM) is one of the activities of the Tridarma of Tinngi College. In this case, this PKM activity was carried out in one of the junior high schools in Tanjung Morawa, namely SMP IT AL IKHWAN Tanjung Morawa. The purpose of this PKM activity is to assist teachers in socializing learning media based on Acehnese culture that can be used in learning, especially for students at the junior high school level. This activity aims to enable teachers to apply Acehl culture-based learning media so that learning in the classroom is more attractive to students. This PKM activity was carried out at SMP IT AL IKHWAN Tanjung Morawa., and was attended by 12 teachers offline (face-to-face). This activity is carried out in 3 stages. The first stage introduces culture-based learning media. The second stage demonstrates the preparation of digital learning media, and the last stage allows teachers to apply learning media in the classroom. The output targets that will be achieved in PKM activities are: (1) teachers can understand Acehnese culture-based learning media, (2) improve teachers' pedagogic competence, (3) teachers can compile digital-based learning media, (4) teachers can apply learning media in the classroom, (5) increase students' interest in learning. The implementation of this PKM went smoothly because all participants were active in the PKM activities and could apply it during the learning process in the classroom.